Investigating the Relationship between Students' Perceptions of English Songs and Measured Learning Outcomes - Jusak Patty; Cindy Itamar Latuihamallo; Hanafi Bilmona (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the correlation between students' perceptions of English songs and their English learning outcomes at SMK Negeri 1 Ambon. Employing a quantitative correlational design, the study involved 33 second-grade students from the Travel and Tourism Business department selected through simple random sampling. Data were collected using a Likert-scale questionnaire measuring students' perceptions of English songs' impact on six language skill areas while learning outcomes were assessed through semester English grades. The findings indicate that students hold highly positive perceptions of English songs as language learning tools (overall mean 3.95), with particularly strong ratings for listening (4.13), reading (4.10), vocabulary (4.07), and speaking (4.05) skills. While 87.9% of students achieved